ANALISIS KETENAGAKERJAAN DI PROVINSI KALIMANTAN TIMUR - YUDHI ARDYAN (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The Main Goal Of this study was to analyze the Employment and determine the influence of Gross Domestic Product and Inflation to Open Unemployment Rate in East Kalimantan province in 2010-2014. The method used is descriptive analysis and multiple linear regression analysis. The results Of this study indicate that the Gross Domestic Product variables have a negative and significant effect on the variable Unemployment Rate with sig t ( 0.035 ) α = 0.05 and variable inflation has a negative influence which is not significant to the variable of Open Unemployment Rate with sig t ( 0248 ) α = 0.05.Keywords: Unemployment, GDP, and Inflation